NUMERICAL ERROR METHOD TO DETERMINE THE EFFICIENCY OF REDUCING VIBRATIONS DUE TO EARTHQUAKE LOADS ON BUILDINGS USING FLUID VISCOUS DAMPER - Prawiro, Radius; Imani, Rafki; Nanda, Nanda (PATTIMURA UNIVERSITY, 2024)
According to The Indonesian Earthquake Map, Padang City in West Sumatra is in Earthquake zone 6. This indicates that Padang City is very vulnerable to earthquakes. Meanwhile, developments in the construction of high buildings also continue to show progress all the time. The main problem that is often faced is the issue of structural damage due to earthquakes. Efforts are needed in earthquake engineering on buildings so that collapse can be minimized. The earthquake damping system used is FVD (Fluid Viscous Dampers) with different types. The Type-A damper is FVD-750 kN and the Type-B damper is FVD-1000 kN, and without using a damper. This research aims to analyze the efficiency of reducing earthquake loads such as floor displacement and vibration period of an 18-story building structure 18 meters high from the base.The analysis method used is a numerical method by calculating earthquake load reduction based on numerical error analysis from the two types of dampers used on structures without using dampers. Building planning refers to SNI 1727-2013, SNI 1726-2019, and SNI 2847-2019, and is assisted by ETABS software. Based on SNI 1726-2019, earthquake risk category II, soft soil condition type (SE), earthquake acceleration response value SDS = 0.745g and SD1 = 0.784g are obtained. The earthquake load used is a dynamic load, taking into account that the condition of the building is irregular. Based on the results of the analysis, it was found that the displacement between floors using the Type-AFVD Damper could reduce the displacement by up to 45.72% and with the Type-B FVD Damper it could reduce the displacement by up to 92.72%. Meanwhile, the period of vibration natural using a Type-A FVD Damper can be reduced by up to 12.34% and using a Type-B FVD Damper can be reduced by up to 33.21%.